A dataset of estimated heterozygous individual and carrier couple frequencies for pan-ancestry carrier screeningMendeley Data - Mia J. Gruzin; Matthew Hobbs; Sarah Poll; Swaroop Aradhya; Leslie Burnett (Data in Brief)
The data described in this publication supported the development and evaluation of pan-ancestry reproductive carrier screening panels for autosomal recessive (AR) and X-linked (XL) conditions.Raw data included combined sets of DNA variants in 1,350 AR/XL genes obtained from the ClinVar and gnomAD databases. The dataset enabled calculations of positive yield for individuals and couples across both ancestry-specific and pan-ancestry, optimised ''Goldilocks''-ranked gene panels, addressing population-specific variations in the frequencies of heterozygous individuals and carrier couples.The positive yield analysis offered a performance metric for carrier screening panels, facilitating the modeling of screening performance for panels of varying sizes and composition and providing resources for optimizing panel content to ensure equity across underrepresented genetic ancestriesThe dataset can support ongoing research into the equitable application of carrier screening and offers significant reuse potential for refining population genetic screening practices, validating computational models, and developing frameworks to update carrier screening panels in alignment with evolving genomic data, including in underrepresented and minority populations.